2019
DOI: 10.1055/s-0039-1697655
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of Group Beta Streptococcus Rectovaginal Cultures at 35 to 37 Weeks of Gestation in Predicting Colonization Intrapartum

Abstract: Objective This study aims to investigate accuracy of group beta Streptococcus (GBS) rectovaginal cultures at 35 to 37 weeks in predicting intrapartum colonization. Study Design Institutional review board (IRB) approved prospective cohort study of 302 women from October 2015 to May 2017. Patients had the following tests for GBS: first trimester urine culture, rectovaginal culture at 35 to 37 weeks, and intrapartum rectovaginal culture. Outcomes included accuracy of 35- to 37-week GBS rectovaginal cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…In a study by McCoy and colleagues, nearly 40% of women that were positive at GBS screening were not GBS positive at the time of admission ( McCoy et al., 2020 ). Alternatively, Hussain et al. (2019) reported a discordance rate of 11%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study by McCoy and colleagues, nearly 40% of women that were positive at GBS screening were not GBS positive at the time of admission ( McCoy et al., 2020 ). Alternatively, Hussain et al. (2019) reported a discordance rate of 11%.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that there may be a benefit to using both sequence-based and culturebased methods to verify presence or absence of low abundance microbes within vaginal microbiome communities. Previous studies have shown discordance in culture-based GBS colonization results between antenatal screening and culture on admission for delivery (McCoy et al, 2020;Hussain et al, 2019). In a study by McCoy and colleagues, nearly 40% of women that were positive at GBS screening were not GBS positive at the time of admission (McCoy et al, 2020).…”
Section: Limited Assessment and Lack Of Focus On Low Abundance Organismsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that there may be a benefit to using both sequence-based and culture-based methods to verify presence or absence of low abundance microbes within vaginal microbiome communities. Previous studies have shown discordance in culture-based GBS colonization results between antenatal screening and culture on admission for delivery 6,58 . In a study by McCoy and colleagues, nearly 40% of women that were positive at GBS screening were not GBS positive at the time of admission 6 Manuscript to be reviewed of 11% .…”
Section: Limited Assessment and Lack Of Focus On Low Abundance Organismsmentioning
confidence: 97%
“…Indeed, it has been shown that GBS carriage fluctuates during the pregnancy and more particularly from 35 to 37 weeks and the onset of labor. Reversion of 35-37 weeks GBS carriage occurs in about 10% of the cases and about 4% of negative GBS carriers are detected as positive at the onset of labor [3]. The use of molecular assays for GBS peripartum screening allows for targeting the correct population with analytical performances equivalent to culture [4].…”
Section: Introductionmentioning
confidence: 99%